The Influence of User Experience and Interface Design Quality on User Satisfaction of FEB UNJ Students with Trust in the Shopee Platform - Siti Nurlaela; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Digital Business and Global Economy, 2025)
This research investigates the impact of User Experience and Interface Design Quality on User Satisfaction of FEB UNJ students, with Trust in the Shopee platform as a mediating variable. Data analysis in this research is executed through the SmartPLS application, applying Partial Least Squares-Structural Equation Modeling (PLS-SEM) within a quantitative design. The respondents consist of FEB UNJ students who are active Shopee users. The results indicate that User Experience and Interface Design Quality have a positive and significant effect on Trust. Furthermore, User Experience, Interface Design Quality, and Trust significantly influence User Satisfaction. Mediation analysis shows that Trust partially mediates the relationship between User Experience and User Satisfaction, as well as between Interface Design Quality and User Satisfaction. These findings highlight the strategic role of trust in strengthening the impact of digital interaction quality on user satisfaction. This study contributes to the literature on digital consumer behavior and provides practical implications for e-commerce platforms in improving service quality and user retention.